2016
DOI: 10.1177/0963721416661173
|View full text |Cite
|
Sign up to set email alerts
|

What a Simple Letter-Detection Task Can Tell Us About Cognitive Processes in Reading

Abstract: Understanding reading is a central issue for psychology, with major societal implications. Over the past five decades, a simple letter-detection task has been used as a window on the psycholinguistic processes involved in reading. When readers are asked to read a text for comprehension while marking with a pencil all instances of a target letter, they miss some of the letters in a systematic way known as the missing-letter effect. In the current article, we review evidence from studies that have emphasized neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
(53 reference statements)
1
10
0
2
Order By: Relevance
“…Fifty years ago, Corcoran (1966) made a stunning discovery: When asked to read a text for comprehension while searching for a target letter, fluent readers of English miss a disproportionate number of e s in the compared with other words. This finding has since been generalized to various words, and the same effect has been found in other languages (Arabic, Chinese, Dutch, French, German, Greek, and Hebrew; for reviews, see Healy, 1994; Klein & Saint-Aubin, in press). Such studies have repeatedly found that readers miss a disproportionately greater number of target letters in function words (which signify grammatical relationships in a sentence) than in content words (which carry meaning).…”
supporting
confidence: 64%
“…Fifty years ago, Corcoran (1966) made a stunning discovery: When asked to read a text for comprehension while searching for a target letter, fluent readers of English miss a disproportionate number of e s in the compared with other words. This finding has since been generalized to various words, and the same effect has been found in other languages (Arabic, Chinese, Dutch, French, German, Greek, and Hebrew; for reviews, see Healy, 1994; Klein & Saint-Aubin, in press). Such studies have repeatedly found that readers miss a disproportionately greater number of target letters in function words (which signify grammatical relationships in a sentence) than in content words (which carry meaning).…”
supporting
confidence: 64%
“…In the present experiment, we accepted the challenge by relating working memory capacity to performance at a letter search task performed while reading for comprehension. Searching for letters in a text is well suited to achieve this goal as targets are surrounded by distractors and the difficulty of the search task naturally varies as a function of reading materials (Klein & Saint-Aubin, 2016). More specifically, it is well known that performance on the search task is influenced by reading processes.…”
mentioning
confidence: 99%
“…More specifically, contrary to Experiment 2, in Experiment 1, function and content words were not equated for length, target letter location, and the frequency difference between function and content words was larger. All these factors are known to influence omission rate (see Guérard et al, 2012; Healy, 1976; Klein & Saint-Aubin, 2016; Roy-Charland et al, 2007). The important point is that despite variations in overall omission rate, the pattern of results was the same as in Experiment 1 with both a missing-letter and a missing-colour effect.…”
Section: Discussionmentioning
confidence: 99%
“…The higher omission rate in function than in content words has been termed by Drewnowski and Healy (1980) as the missing-letter effect and it is thought to reflect readers’ allocation of attention to the text (Roy-Charland et al, 2007). This missing-letter effect has been found in many languages (Arabic, Chinese, Dutch, French, German, Greek, and Hebrew) and emerged as soon as in Grade 1 (for an overview see Klein & Saint-Aubin, 2016). The ubiquity of the missing-letter effect fits well with the psycholinguistic literature showing that the distinction between content and function words pervades all languages (Abney, 1987) and across development (e.g., Shi et al, 1999).…”
mentioning
confidence: 89%